Technoscience and Racial Contract in Francophone Africa : Epistemological and Political Challenges - KITI, PAUL CHRISTIAN (My University, 2022)
In spite of the nobility of its ambitions, science, as far as its acquisition, strategic distribution and use are concerned, has not always been as reasonable as expected. In Francophone Africa, the issue of science has much to do with racial and historical considerations. As we reflect on African studies and the Fourth Industrial Revolution, we cannot, as Africans, undermine the epistemological and the political issues which surround the question of science in Africa. These issues are prerequisites to the genuine grasp of the 4IR (Forth Industrial Revolution). In Africa, francophone countries seem to be more confronted with such problems. Most of them are still among the poorest countries of the world. What is science and what is racial contract ? How is science affected by racial and imperialist considerations in Africa ? Which are the epistemological and the political manifestations of the African scientific extraversion and underdevelopement ? Which are the ways forward today? These are the main questions we have tried to respond to in this paper.
Keywords: Science; Racial Contract; Francophone Africa; Epistemology; Politics